Pelatihan Persiapan Pembelajaran Geometri Bagi Guru Kelas Rendah Pada Program Organisasi Penggerak Propinsi NTT - Irna Karlina Sensiana Blegur (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
The purpose of this Community Service (PkM) activity is to train lower grade elementary school teachers in the “Program Organisasi Penggerak (POP)” of East Nusa Tenggara Province (NTT) related to prepare teaching materials and methods of geometry based on four levels of learning activities according to Realistic Mathematics Education. The PkM team from Mathematics Education Study Program, Nusa Cendana University, collaborated with the POP coordinator so that there were nine lower grade teachers and Principal of Elementary School who actively participated. This activity was carried out through two phases: preparation and implementation. In the preparatory phase, an initial survey through the work of several questions and unstructured interviews was carried out in order to obtain data that became the basis for implementation phase. For the implementation phase, activities were carried out classically for two days in the network. Discussion, question-answer and hands-on practice were the methods used during the implementation phase. There were 5 sub topics discussed in this phase. The characteristics geometry and some concepts of solid geometry on the first day, meanwhile some others topics about plane geometry on the second day. The results of the evaluation indicate that this training has succeeded in achieving the purpose.